Dilema Kriminalisasi Kebijakan Publik dalam Korupsi: Batas Kegagalan dan Maladministrasi - Nur Misyuari Maddolangeng (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2026)
The enforcement of anti-corruption laws in Indonesia often faces programmatic distortion when dealing with public policy outcomes. This article examines the systemic shift from administrative failures into criminal liabilities within the framework of Indonesian criminal law, particularly focusing on Articles 2 and 3 of the Anti-Corruption Act (UU Tipikor). Utilizing a normative-legal method with a dogmatic-criminal approach, this study analyzes how law enforcement constructs the element of wederrechtelijk (unlawfulness) in policy-driven cases. The findings indicate a dangerous expansion of criminal dogmatics where technical-managerial errors are directly equated with criminal unlawfulness without establishing a distinct legal causation (causalitas) to the financial loss. This study argues that the criminal court must maintain strict dogmatic boundaries to prevent anti-corruption laws from becoming a tool of retroactive criminalization against executive decisions.